Penggunaan Teknik Modeling Simbolik Untuk Meningkatkan Kepercayaan Diri Siswa Tunagrahita Ringan Kelas VIII Di SLB Negeri 1 Bulukumba - Nuraidah; Abdullah Pandang; Sahril Buchori (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2024)
This study examines the low self-confidence of mildly disabled students at SLB Negeri 1 Bulukumba. The formulation of the problems in this study are (1) What is the description of the behavior of self-confidence of mildly retarded students in class VIII at SLB Negeri 1 Bulukumba based on the analysis of the initial condition/baseline 1 (A1); (2) How is the description of the implementation of modeling techniques in increasing the self-confidence of mildly retarded students in class VIII at SLB Negeri 1 Bulukumba in the intervention condition (B); (3) Whether modeling techniques can increase the self-confidence of mildly retarded students in class VIII at SLB Negeri 1 Bulukumba based on the results of the analysis of the final condition of baseline 2 (A2)."The purpose of this study was to determine: (1) self-confidence of mildly disabled students before being given intervention (Baseline 1/A1); (2) self-confidence of mildly disabled students when given intervention (B); (3) self-confidence of mildly disabled students after being given intervention (Baseline 2/A2); and (4) fine motor skills of students based on analysis between conditions before being given intervention, when given intervention, and after being given intervention. The data collection technique used is an action test. The subject in this study was one student with Down syndrome whose initials were RMR. This study uses an experimental method that uses Single Subject Research (SSR) with the A-B-A design: (1) Students' fine motor skills before being given treatment are very low based on the results of the analysis in baseline 1 (A1); (2) Students' fine motor skills during treatment have increased to the high category seen from the results of the analysis in the intervention condition (during treatment); (3) Students' fine motor skills after being given treatment increased to the sufficient category seen from the results of the analysis in the condition at baseline 2 (A2) or after treatment. Thus, students' fine motor skills after being given treatment increased due to the effect of providing intervention.